Molecular characteristics of leonardite humic acid and the effect of its fractionations on sulfamethoxazole photodegradation. (May 2020) - Zhang, Yiyue; Zhao, Furong; Wang, Fei; Zhang, Yahe; Shi, Quan; Han, Xiaomin; Geng, Huanhuan
Abstract: The widespread occurrence of synthetic antibiotic sulfamethoxazole (SMX)— poses a potential risk to aquatic ecosystems where dissolved organic matter (DOM) may affect its photolysis. In this study, the elimination of SMX by solar photolysis was investigated in the presence of leonardite humic acid (LHA) and its fractions. Fourier transform ion cyclotron resonance mass (FT-ICR-MS) spectra showed that LHA has high aromaticity. van Krevelen diagrams demonstrated highly unsaturated and phenolic compounds. The photolytic degradation of SMX was impeded by all DOM, mainly due to the competition of photons and scavenging or quenching of reactive oxygen species (ROS). The evaluation of isolated fractions of LHA suggested that fractions with MW < 3500, 14000–25, 000 and > 100, 000 had the greatest negative effects on sulfamethoxazole photodegradation; their inhibitory activities could reach up to 56.2%, 52.9% and 50.5%, respectively. The characterization of DOM at the molecular level will provide further insights into the assessment of photolysis for antibiotic elimination in natural waters where DOM exists ubiquitously. Graphical abstract: Image 1 Highlights: FT-ICR-MS spectra showed that LHA has high aromaticity. OH,   1 O2  and O2 - all make a contribution to SMX photodegradation. LHA inhibited the photodegradation of SMX profoundly. Different molecular weight of LHA has significant impact on SMX photolysis.